Jack Ward Thomas : the journals of a Forest Service chief - Thomas, Jack Ward (Forest History Society : in association with University of Washington Press, 2004)
"Jack Ward Thomas, an eminent wildlife biologist and U.S. Forest Service career scientist, was drafted in the late 1980s to head teams of scientists to develop strategies for managing the habitat of the northern spotted owl. That assignment led to his selection as Forest Service chief during the early years of the Clinton administration. It is history's good fortune that Thomas kept journals of this thoughts and daily experiences, and that he is a writer able to capture the moment with clarity and grace."